2020
DOI: 10.1038/s41598-020-63188-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased O-GlcNAcylation rapidly decreases GABAAR currents in hippocampus but depresses neuronal output

Abstract: O-GlcNAcylation, a post-translational modification involving O-linkage of β-N-acetylglucosamine to Ser/Thr residues on target proteins, is increasingly recognized as a critical regulator of synaptic function. Enzymes that catalyze O-GlcNAcylation are found at both presynaptic and postsynaptic sites, and O-GlcNAcylated proteins localize to synaptosomes. An acute increase in O-GlcNAcylation can affect neuronal communication by inducing long-term depression (LTD) of excitatory transmission at hippocampal CA3-CA1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…An acute increase in N-acetylglucosamine glycosylation can affect neuronal communication by inducing long-term depression of excitatory transmission at hippocampal synapses, as well as suppressing hyperexcitable circuits in vivo [36,37]. In addition, N-acetylglucosamine glycosylation reduces action potential probability in pyramidal cells [36]. These findings from previous trials may help explain the improvements in depressive symptoms noted in the present trial.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…An acute increase in N-acetylglucosamine glycosylation can affect neuronal communication by inducing long-term depression of excitatory transmission at hippocampal synapses, as well as suppressing hyperexcitable circuits in vivo [36,37]. In addition, N-acetylglucosamine glycosylation reduces action potential probability in pyramidal cells [36]. These findings from previous trials may help explain the improvements in depressive symptoms noted in the present trial.…”
Section: Discussionsupporting
confidence: 63%
“…Although unexplored, this is a possible mechanism for the favorable effects of liquid vinegar ingestion on insulin sensitivity noted in human trials. Moreover, and pertinent to the present trial, the brain contains some of the highest levels of N-acetylglucosamine glycated proteins in the body, with the hippocampus expressing high levels of N-acetylglucosamine transferase and N-acetylglucosaminase [36]. An acute increase in N-acetylglucosamine glycosylation can affect neuronal communication by inducing long-term depression of excitatory transmission at hippocampal synapses, as well as suppressing hyperexcitable circuits in vivo [36,37].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Increased autophagic flux has also been reported with TG administration in drinking water at 500 mg/kg/d for 2 weeks to RFP-GFP-LC3 mice [24]. In addition to apparently divergent effects on neuronal autophagy, an acute increase in O-GlcNAcylation levels in vivo impairs learning and memory [25] and it has been reported that protein O-GlcNAcylation is a regulator of neuronal excitability [25][26][27]. In other excitable cells, such as cardiomyocytes, increases in mitochondrial O-GlcNAc levels have been reported to increase oxidative phosphorylation as well as lead to impaired mitochondrial function [28][29][30].…”
Section: Introductionmentioning
confidence: 90%
“…To date, the majority of the studies related to the effects of increased O-GlcNAc in the brain have focused on chronic disease models or prolonged treatment with OGA inhibition, despite the fact that as discussed above short-term treatment with OGA inhibitors can have acute neurological effects [25][26][27]. We have recently shown that only 3 h after a single treatment with the OGA inhibitor thiamet G there was marked increases in O-GlcNAcylation (> 1.5-fold) of 65 proteins [35].…”
Section: Introductionmentioning
confidence: 99%